Training Needs of Grass-Root Level Extension Worker - Kumari Kavita , Dibyanshu Shekhar; A. K. Singh (Indian Journal of Extension Education, 2017)
The multiplicity of extension systems are under operation in India considering the varied agro-ecological situations under which farmers reside, besides variations in the resource base of farmers. The extension system envisaged to achieve desired growth in agricultural sector with pluralistic in nature. Visualizing the need to deploy trained man power at grass root level for ensuring effective extension, the Government of Bihar state appointed Agriculture Coordinator and Kisan Salahkar at panchayat level to cater the farmers’ information need and to assist the farmers for giving them advantages of ongoing agricultural developmental programmes. Training needs for grass root level extension personnel can be defined in terms of gap between job requirement and job performance. During the study the training need was assessed in the thematic areas like improved agricultural practices, organization and administration, programme development and execution, communication skill and social system and local leadership with the help of Agriculture Coordinator and Kisan Salahkar as the sample. The results of the study reveal that perceived training about improved agricultural technology was very much needed by the 73.33 per cent of the Agriculture Coordinator, whereas 87.79 per cent of Kisan Salahkar were also showed the same pattern of this responses